International Trade and Structural Unemployment: Evidence from the OECD countries - Barbosa, Rui (2020)
This paper seeks to investigate the possible relationship between a country’s structural rate of unemployment and its relative openness to international trade. To that end, we regress a data panel of unemployment and trade openness for the 36 member-states of the OECD, controlling for business cycle and labor market structure effects. No evidence that higher openness to international trade has unemployment increasing effects, on average, in the OECD countries is found.